Model Strategi Pengelolaan Badan Usaha Milik Desa pada Era Pandemi Covid-19 di Kabupaten Malang - Yuntawati Fristin; Akbar Pandu Dwinugraha (Jurnal Administrasi Bisnis, 2023)
Even though the current Covid-19 pandemic has subsided, most BUMDesa in Malang Regency, East Java Province, are still experiencing the remnants of the difficulties they faced when the Covid-19 pandemic was rampant in Indonesia to remote villages. The existence of a management model has a very important role in helping the development of Village-Owned Enterprises (BUMDesa) This research uses a combination type of research (mix methode). The time for collecting research data is in the period June - September 2022. Research data collection techniques use interviews and open electronic questionnaires. Data analysis uses Process Hierarchy Analytics (PHA) combined with SWOT analysis. Village-owned enterprises in this case are no exception from BUMDesa thanks to the category of Developing and Advanced Stubs. the three bumdesa experienced problems related to the existence of PPKM which was regulated by the government. Fortunately, the existing bumdesa still have strengths and advantages that can be used to overcome the challenges that arise. Diversification is one of the efforts that can be done to further encourage the strength possessed to overcome incoming challenges. The diversification includes product diversification of market segmentation sales patterns and also human resource management. The development strategy model of village-owned enterprises categorized as developing and advanced startups needs to pay attention to the application of the diversification model. Diversification is one of the efforts that can be done to further encourage the strength possessed to overcome incoming challenges. The diversification includes product diversification of market segmentation sales patterns and also human resource management